In the public domain : presidents and the challenges of public leadership - Han, Lori Cox; Heith, Diane J. (SUNY series on the presidency., 2005)
The "public presidency"--How presidents rely on the mass media, public opinion, and various communication strategies-has become an increasingly important aspect of presidential governance and leadership during the past two decades. In the Public Domain gathers together noted presidency and communication scholars to explore the relationship between the president and the American public, the current state of the "public presidency," and the challenges that recent presidents have faced in developing an effective means of communicating and maintaining a strong presidential image. Specific topics include: how presidents use public leadership to pursue their policy goals and objectives; the importance of public opinion, rhetorical strategies, and public activities; external factors such as party politics and news media coverage; the cultivation of presidential legacy; and access to documents in presidential libraries